Peran Masyarakat dan BPBD Kebumen dalam Penanggulangan Banjir di Kecamatan Padureso - Dewi, Aliffina Yulianoor Rinto; Juhadi, Juhadi; Suharini, Erni; Putro, Saptono (Journal of Applied Geoscience and Engineering, 2024)
The purpose of this research is to determine the level of knowledge of the people of Padureso District regarding efforts to manage flood disasters in Padureso District, Kebumen Regency, to find out the form of participation of the community and the Regional Disaster Management Agency (BPBD) of Kebumen Regency in flood disaster management efforts in Padureso District, Kebumen Regency, and to find out the effectiveness The role played by the community and the Regional Disaster Management Agency (BPBD) of Kebumen Regency in efforts to overcome flood disasters in Padureso District, Kebumen Regency by Law No. 24 of 2007. The research carried out was quantitative research and data analysis techniques used descriptive analysis. The results of the research show that the level of knowledge of the people of Baligasal Village and Merden Village is relatively low, causing the implementation of the community's role in flood disaster management efforts to be less than optimal. The form of participation of the Baligasal Village and Merden Village Community as well as the Kebumen Regency BPBD in flood disaster management efforts is material participation in the form of money and goods, as well as non-material participation in the form of thoughts, energy, and skills. The effectiveness of the role carried out by BPBD Kebumen Regency in flood disaster management efforts is by Law Number 24 of 2007 concerning Disaster Management, namely achieving the objectives of the development-based disaster risk reduction program through the formation of Disaster Resilient Villages. (destana), integration capacity to coordinate and communicate with the village government to carry out socialization about disasters in villages that have been formed into villages, and adaptive capacity to work together with elements of society to realize participation in disaster management efforts in their area.